Feasibility, safety, and outcome of endovascular recanalization in childhood stroke: the save childS Study - Sporns, Peter B.; Sträter, Dirk Ronald; Minnerup, Jens; Wiendl, Heinz; Hanning, Uta; Chapot, René; Henkes, Hans; Henkes, Elina; Grams, Astrid; Dorn, Franziska; Nikoubashman, Omid; Wiesmann, Martin; et al. (JAMA neurology, 2020)
Randomized clinical trials have shown the efficacy of thrombectomy of large intracranial vessel occlusions in adults; however, any association of therapy with clinical outcomes in children is unknown. Objective To evaluate the use of endovascular recanalization in pediatric patients with arterial ischemic stroke. Design, Setting, and Participants This retrospective, multicenter cohort study, conducted from January 1, 2000, to December 31, 2018, analyzed the databases from 27 stroke centers in Europe and the United States. Included were all pediatric patients (<18 years) with ischemic stroke who underwent endovascular recanalization. Median follow-up time was 16 months. Exposures Endovascular recanalization. Main Outcomes and Measures The decrease of the Pediatric National Institutes of Health Stroke Scale (PedNIHSS) score from admission to day 7 was the primary outcome (score range: 0 [no deficit] to 34 [maximum deficit]). Secondary clinical outcomes included the modified Rankin scale (mRS) (score range: 0 [no deficit] to 6 [death]) at 6 and 24 months and rate of complications. Results Seventy-three children from 27 participating stroke centers were included. Median age was 11.3 years (interquartile range [IQR], 7.0-15.0); 37 patients (51%) were boys, and 36 patients (49%) were girls. Sixty-three children (86%) received treatment for anterior circulation occlusion and 10 patients (14%) received treatment for posterior circulation occlusion; 16 patients (22%) received concomitant intravenous thrombolysis. Neurologic outcome improved from a median PedNIHSS score of 14.0 (IQR, 9.2-20.0) at admission to 4.0 (IQR, 2.0-7.3) at day 7. Median mRS score was 1.0 (IQR, 0-1.6) at 6 months and 1.0 (IQR, 0-1.0) at 24 months. One patient (1%) developed a postinterventional bleeding complication and 4 patients (5%) developed transient peri-interventional vasospasm. The proportion of symptomatic intracerebral hemorrhage events in the HERMES meta-analysis of trials with adults was 2.79 (95% CI, 0.42-6.66) and in Save ChildS was 1.37 (95% CI, 0.03-7.40). Conclusions and Relevance The results of this study suggest that the safety profile of thrombectomy in childhood stroke does not differ from the safety profile in randomized clinical trials for adults; most of the treated children had favorable neurologic outcomes. This study may support clinicians’ practice of off-label thrombectomy in childhood stroke in the absence of high-level evidence.